Sanity of corn grains as a function of genetic material - Oliveira, L. F.; Donato, J. V.; Ruffato, S.; Bonaldo, S. M. (Scientific Electronic Archives, 2018)
Diseases that occur in corn crops can cause great losses to farmers and consumers of its product and derivatives. So, was evaluated the sanity of maize grains in different genetic materials. The grains used were obtained from the crop of 2014/2015 on a farm in the city of Sorriso, State of Mato Grosso. For this, grain samples were collected from hybrids P3630H, 30F53YH, P2830H, and P3844H. The standard test ("Blotter Test") allowed noticing the incidence of Aspergillus sp., Fusarium sp. and Penicillium sp. Data were submitted to analysis of variance and Scott-Knott test at 5% probability. In treatments with the resistant genetic material the genus with the highest incidence was Penicillium sp. (82%), followed by Fusarium sp. (68.75%) and Aspergillus sp. (15.25%). The hybrid with the lower incidence of Fusarium sp. was P2830H (59%). The hybrid with greater resistance to Aspergillus sp. and Penicillium sp. was P3844H (5 and 55%, respectively). The most susceptible hybrid to pathogens Aspergillus sp., Fusarium sp. and Penicillium sp. was 30F53YH (37, 79 and 94%, respectively). For the better sanitary quality of grains, based on the observed data, it is recommended to use the hybrid P2830H